2000
DOI: 10.1021/ja993689k
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Photoinduced Charge Separation and Charge Recombination in Synthetic DNA Hairpins with Stilbenedicarboxamide Linkers

Abstract: The dynamics of photoinduced charge separation and charge recombination in synthetic DNA hairpins have been investigated by means of femtosecond and nanosecond transient spectroscopy. The hairpins consist of a stilbene linker connecting two complementary 6-mer or 7-mer oligonucleotide strands. Base pairing between these strands results in formation of hairpins in which the stilbene is approximately parallel to the adjacent base pair. The singlet stilbene is selectively quenched by guanine, but not by the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
259
1
3

Year Published

2000
2000
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(287 citation statements)
references
References 75 publications
24
259
1
3
Order By: Relevance
“…Some fluorophores conjugated DNA were reported to quench its fluorescence upon hybridization by photoinduced electron transfer accompanying DNA damage, such as irreversible electron transfer with guanine and/or DNA cleavage. 13,[25][26][27][40][41][42][43][44] These matters are greatly related to recent topics of DNA electron transfer, 45 but are too complicated to understood. Some researchers examined both forward and reverse electron transfer in the photoinduced electron transfer process, e.g.…”
Section: Several Dye-labeled Dna Probe and Its Quenching By Hybridizamentioning
confidence: 99%
“…Some fluorophores conjugated DNA were reported to quench its fluorescence upon hybridization by photoinduced electron transfer accompanying DNA damage, such as irreversible electron transfer with guanine and/or DNA cleavage. 13,[25][26][27][40][41][42][43][44] These matters are greatly related to recent topics of DNA electron transfer, 45 but are too complicated to understood. Some researchers examined both forward and reverse electron transfer in the photoinduced electron transfer process, e.g.…”
Section: Several Dye-labeled Dna Probe and Its Quenching By Hybridizamentioning
confidence: 99%
“…Numerous experimental studies have been performed, resulting in reports of widely varying distance dependences of the electron transfer. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Some of the experimental systems studied appear to undergo almost distance-independent electron transfer. [4][5][6][7][8][9][10] Theories to explain this work include pair wise hopping mechanisms, 15 wavelike electron transfer through a delocalized bridge system, 16 and thermally activated pair wise transfer via base pairs.…”
Section: Introductionmentioning
confidence: 99%
“…17 Some experimental work shows a distance dependence typical of superexchange or electron tunneling (Marcuslike) observed for inter-and intramolecular electron transfer in a wide variety of environments, including proteins, liquids, and micelles. [1][2][3][11][12][13][14] It has recently been suggested that electron transfer in DNA may occur by different mechanisms depending on the energetics of a specific system. 15 The focus of this paper is to examine the role played by the distance dependence of the reorganization energy and the free energy associated with electron transfer on the overall distance dependence of single-step electron transfer (Marcus-like transfer) in the heterogeneous DNA environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wealth of experimental evidence has established, undeniably, that DNA can act as a conduit for rapid and long-range charge transfer (CT), not only in DNA assemblies designed in the laboratory (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), but also in biologically significant environments (25,26). DNA, remarkable for its role in the molecular basis of life, may also play a role as a mediator of CT in diverse areas of chemistry and biology.…”
mentioning
confidence: 99%